Co-inquiry with students: When shared questions lead the way (Teaching and Learning Inquiry, 2016)
Co-inquiry represents a distinctive relational model for partnering with students in SoTL that focuses on the process of seeking itself, and in particular, the importance of shared questions. We use case studies from two institutions to illustrate co-inquiry in action and highlight the importance of shared questions in changing the faculty-student dynamic in ways that foster deep learning. Clarifying the nature of co-inquiry around shared questions represents a valuable way to effectively strengthen and enrich learning not only for students, but also for everyone involved in SoTL partnerships with students. The programs described here illustrate how co-inquiry can work as a form of institutional SoTL, providing valuable and authentic opportunities to incorporate student voices—and shared questions—in effecting institutional change.